Geological and thermochronological studies of the Dashui gold deposit, West Qinling Orogen, Central China - Zeng, Q.; Evans, Noreen; McInnes, Brent; Batt, G.; McCuaig, T.; Bagas, L.; Tohver, E. (Springer, 2013)
The Dashui gold deposit is a structurally controlled, Carlin-type gold deposit hosted by recrystallised limestone in the West Qinling Orogen of Central China. The major, structurally late east-trending Dashui Fault forms the hanging wall to the gold mineralisation at the Dashui mine and defines the contact between Middle Triassic limestone and a steeply dipping overlying succession of Middle Triassic argillaceous limestone, dolomite, and sandstone. Multiple carbonate veins and large-scale supergene enrichment, represented by hematite, goethite, limonite and jarosite, characterise the deposit. Detailed geochronological investigation using zircon SHRIMP U-Pb dating reveals that volcanic rocks closely associated with the Dashui gold deposit were synchronous with the Ge’erkuohe Granite and pre-date mineralisation. The igneous dyke sample from the hanging wall has the same U-Pb zircon age as the footwall, ca. 213 Ma. (U-Th)/He thermochronology on dykes in the hanging wall and footwall of the Dashui Fault yields identical (U-Th)/He zircon ages of ca. 210 Ma but distinct (U-Th)/He apatite ages of ca. 136 and 211 Ma, respectively.Therefore, the hanging wall and footwall are interpreted as having distinct post-mineralisation exhumation histories. Reverse fault movement exhumed the hanging wall ~2 to 4 km since the Late Triassic with the main component of faulting taking place between the Late Triassic and Early Cretaceous. These relationships suggest a Late Triassic to Early Cretaceous age for the primary gold mineralisation at the Dashui gold deposit, with the corollary that any ‘missing portion’ of the deposit, previously hypothesised to exist in the hanging wall of the Dashui Fault, has been eroded away. The mineralisation in the footwall may have been supergene enriched soon after the primary mineralisation was emplaced, because it has been located at shallow depth since the Late Triassic. Semi-quantitative results obtained in this study also constrain the maximum depth of formation of the Dashui gold at no more than 2 km.